Mitotic activity in the oral epithelium of the albino rat - Cleaton-Jones, P. (My University, 1976)
In groups of Wistar rats 3 and 12 months of age, colchicine and radioautography were used to assess mitotic activity in oral epitheliums. Apparent mitotic activity in the epitheliums of the cheek, hard palate, and central, intermediate, and lateral zones of the soft palate depended on the method used and the age of the rat.
Keywords: Mouth Mucosa; Mitosis; Rats